2023
DOI: 10.1021/acs.est.2c05009
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Associating with Carbon and Nitrogen Metabolism during Biodegradation of Polyethene in Tenebrio larvae with Crop Residues as Co-Diets

Abstract: Tenebrio molitor and Tenebrio obscurus (Coleoptera: Tenebrionidae) larvae are two commercial insects that eat plant and crop residues as diets and also biodegrade synthetic plastics polyethylene (PE). We examined biodegradation of low-density PE (LDPE) foam (M n = 28.9 kDa and M w = 342.0 kDa) with and without respective co-diets, i.e., wheat brain (WB) or corn flour (CF), corn straw (CS), and rice straw (RS) at 4:1 (w/w), and their gut microbiome and genetic metabolic functional groups at 27.0 ± 0.5 °C after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Recently, evidence for nitrogen fixation has been found during the degradation of PS, LDPE, and PET by T. molitor larvae. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, evidence for nitrogen fixation has been found during the degradation of PS, LDPE, and PET by T. molitor larvae. ,, …”
Section: Resultsmentioning
confidence: 99%
“…70 Recently, evidence for nitrogen fixation has been found during the degradation of PS, LDPE, and PET by T. molitor larvae. 38,56,71 The analysis of gut microbial communities showed that various microorganisms in T. molitor larvae degrade polymers with different MW of PP polymers, yet the main functions of intestinal microorganisms in the process of plastic degradation are unified. This finding implies that the intestinal microbial community of T. molitor larvae contributes to PP biodegradation by forming a system conducive to plastic degradation domesticated through ingesting polymers.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Solid oxide fuel cells can also be used to generate electricity, and this electricity can be sold at a good price 52 . Additionally, the by‐product of farm waste can be used to improve the soil conditions 53–56 . But, careful consideratons need to be given to heavy metals found in waste 57,58 …”
Section: Resultsmentioning
confidence: 99%
“…52 Additionally, the by-product of farm waste can be used to improve the soil conditions. [53][54][55][56] But, careful consideratons need to be given to heavy metals found in waste. 57,58…”
Section: Economic Analysismentioning
confidence: 99%
“…They are made commercially for use as pet food for birds and reptiles and fishing bait [9]. As a result of their high nutritious value and low contamination levels, mealworm larvae are a particularly sustainable source of feed and food [10,11]. Exudates, feces, body parts, and dead insects contaminate plant products [12,13].…”
Section: Introductionmentioning
confidence: 99%